Reluctant sleuths, true detectives - Jacobs, Jason (Albany : State University of New York Press, 2023)
Explores the figure of the detective as a pursuer of knowledge in four noir films.
Introduction: The Long Goodbye -- The Long Goodbye: Floating above the Genre -- 1 Out of the Past -- "All I can see is the frame." -- 2 Notorious -- 3 Vertigo -- 4 Chinatown -- Conclusion: True Detectives
Includes bibliographical references and index.
Online resource title from digital title page; (viewed on March 6, 2023)
JSTOR
Keywords: Out of the past (Motion picture : 1947); Notorious (Motion picture : 1946); Vertigo (Motion picture : 1958); Chinatown (Motion picture); Chinatown (Motion picture); Out of the past (Motion picture : 1947); Vertigo (Motion picture : 1958); Detective and mystery films -- United States -- History and criticism; Film noir -- United States -- History and criticism; Knowledge, Theory of, in motion pictures; Motion pictures -- Philosophy; Films de détective -- États-Unis -- Histoire et critique; Films noirs -- États-Unis -- Histoire et critique; Théorie de la connaissance au cinéma.; Cinéma -- Philosophie; PERFORMING ARTS / Film & Video / History & Criticism; Detective and mystery films; Film noir; Knowledge, Theory of, in motion pictures; Motion pictures -- Philosophy; United States; Electronic books; Criticism, interpretation, etc